2016
DOI: 10.3928/02793695-20160817-05
|View full text |Cite
|
Sign up to set email alerts
|

Managing Workplace Violence With Evidence-Based Interventions: A Literature Review

Abstract: Workplace violence in health care settings is an occupational issue concerning nurses and other health care professionals. Patient aggression against nurses is often the most common form of violence in clinical settings, occurring in emergency departments, inpatient psychiatric settings, and nursing homes. Physical and verbal assaults are the major forms of workplace violence encountered by nurses. Current research has identified staff, environmental, and patient risk factors as the major precursors of workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 15 publications
3
64
0
6
Order By: Relevance
“…Also directing any interventions towards the younger and inexperienced nurses, who are the most vulnerable and the most exposed to violence (Gillespie, Gates, Miller, & Howard, ). Investing in physical barriers and adopting appropriate architectural measures is an effective strategy (Martinez, ). Although there is still no evidence of effectiveness that can support specific interventions to counteract WPV (McPhaul, London, & Lipscomb, ), some studies have shown the greater effectiveness of comprehensive approaches, compared to individual targeted interventions (Ramacciati, Bambi, et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also directing any interventions towards the younger and inexperienced nurses, who are the most vulnerable and the most exposed to violence (Gillespie, Gates, Miller, & Howard, ). Investing in physical barriers and adopting appropriate architectural measures is an effective strategy (Martinez, ). Although there is still no evidence of effectiveness that can support specific interventions to counteract WPV (McPhaul, London, & Lipscomb, ), some studies have shown the greater effectiveness of comprehensive approaches, compared to individual targeted interventions (Ramacciati, Bambi, et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation could be that hospitals with more violence in the workplace provide more training. However, the lack of data on the type, quality and effectiveness of communication training courses is a limitation that must be considered when analysing the correlation between violence risk and training (Martinez, ). Longitudinal or experimental studies can usefully disclose the impact of a training intervention on the reduction of violent episodes (Beech, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for workplaces to adopt evidence‐based interventions (e.g. consumer/patient risk assessments, staff education and training, aggression/violence management teams) that can enhance staff safety within the healthcare environment in such a way that it limits violence against healthcare workers (Hills & Joyce ; Martinez ; Morphet et al ). In addition, increasing the visibility and awareness of these issues and building healthcare worker resiliency, through approaches like trauma‐informed self‐care, can further lower BO and STS (Beattie et al ; Dzau et al ; Salloum et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence (WPV) in healthcare settings has been drawing attention for over 20 years [2,[4][5][6][7][8] and has been reported in many places, including Europe [9], Asia [10][11][12], the U.S. [13], and the Middle East [14]. According to a recent review, the prevalence of WPV against healthcare workers was higher in Asian and North American countries than that in other countries [15].…”
Section: Introductionmentioning
confidence: 99%